2012
DOI: 10.1016/j.lungcan.2011.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and risks of using erythropoiesis-stimulating agents (ESAs) in lung cancer patients: Study-level and patient-level meta-analyses

Abstract: In anemic patients receiving myelosuppressive chemotherapy, erythropoiesis-stimulating agents (ESAs) raise hemoglobin levels and reduce transfusion requirements, but ESA-related safety concerns exist. To evaluate ESA benefits and risks in lung cancer, we conducted meta-analyses of data from controlled ESA trials conducted in lung cancer patients. Study-level analyses included controlled ESA trials reporting lung cancer mortality, identified from the 2006 Cochrane ESA report and from a systematic search for stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 39 publications
2
33
1
Order By: Relevance
“…During the follow-up period, a significantly higher incidence of death from lung ADC was found in patients with low pretreatment EPOR levels as compared with those of high EPOR levels. Although large-scale meta-analyses of clinical trials on erythropoiesis-stimulating agents in various tumor types [28], including NSCLC [29], suggest no effect of these drugs on patients' prognosis, our results, therefore, support an effect of rHuEPOα either directly or indirectly reducing pulmonary ADC progression. The current preliminary study, however, has to be confirmed in further studies in additional cohorts of patients with lung ADC.…”
Section: Discussioncontrasting
confidence: 47%
“…During the follow-up period, a significantly higher incidence of death from lung ADC was found in patients with low pretreatment EPOR levels as compared with those of high EPOR levels. Although large-scale meta-analyses of clinical trials on erythropoiesis-stimulating agents in various tumor types [28], including NSCLC [29], suggest no effect of these drugs on patients' prognosis, our results, therefore, support an effect of rHuEPOα either directly or indirectly reducing pulmonary ADC progression. The current preliminary study, however, has to be confirmed in further studies in additional cohorts of patients with lung ADC.…”
Section: Discussioncontrasting
confidence: 47%
“…For example, in a pooled analysis of randomized, double-blind, placebo-controlled trials in patients with chemotherapy-induced anemia receiving DA or placebo (n=2122), DA had no impact on mortality, progression-free survival or disease progression [14]. Similarly, three metaanalyses -one of studies in patients with lymphoproliferative malignancies [15], one in patients with lung cancer [16] and one broader analysis of oncology studies [17] -found no effect of ESAs on survival or disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…The latter effectively eliminated the use of ESAs in patients being treated for cure. Although significant controversy exists regarding the impact of ESA use on survival in cancer patients with CAA, the impact of FDA and CMS policy on ESA use is clear [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%